Eclecticism of Voter Characteristics and Electoral Choices in Indonesia: Lessons from the 2024 Indonesian Presidential Election - Suryanagara, Muhammad Iftitah Sulaiman; Rahmatunnisa, Mudiyati; Bainus, Arry; Umam, Ahmad Khoirul (Journal of Posthumanism, 2025)
This study underscores the eclectic nature of voter characteristics in shaping electoral choices in Indonesia’s 2024 Presidential Election. By exploring a multidimensional framework encompassing demographic, sociological, psychosocial, and rational factors, it reveals the intricate dynamics influencing voter preferences. Utilizing a survey of 1,800 eligible voters across Indonesia, the study employs cross-tabulation and Chi-square tests to uncover significant associations between voter traits and candidate selection. The findings highlight the pivotal roles of age and income as demographic determinants, with younger voters and higher-income groups showing distinct preferences. Sociologically, religious and ethnic identities are profoundly influential, reflecting the continued salience of these affiliations in Indonesia’s political landscape. Psychosocial elements, such as opinion leaders and party affiliations, further underscore their mediating effects on voter behaviour, bridging individual perceptions with broader sociopolitical contexts. Rational evaluations of candidates' competencies and track records emerge as critical drivers of electoral decisions, emphasizing the pragmatic dimensions of voter behaviour. By integrating these diverse elements, the study presents a comprehensive view of voter decision-making processes, offering valuable lessons for tailoring campaign strategies. It enriches the discourse on Indonesian electoral behaviour, advocating for nuanced approaches that address the multifaceted interplay of identity, influence, and rationality in shaping political outcomes.